2017
DOI: 10.1007/s00726-017-2478-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cationic amino acid transporters in pig skeletal muscles during postnatal development

Abstract: The cationic amino acid transporter (CAT) protein family transports lysine and arginine in cellular amino acid pools. We hypothesized that CAT expression changes in pig skeletal muscles during rapid pig postnatal development. We aimed to investigate the tissue distribution and changes in the ontogenic expression of CATs in pig skeletal muscles during postnatal development. Six piglets at 1, 12, 26, 45, and 75 days old were selected from six litters, and their longissimus dorsi (LD), biceps femoris (BF), and rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…In a previous study, we found a difference in the postnatal expression pattern of CAT-1 and CAT-2A, as well as differences in CAT-2A expression levels among LD, BF, and RH muscles (Ishida et al 2017). Here, we compared the effects of a low-protein diet and feed restriction on the expression of CAT-1 and CAT-2A among three skeletal muscles of growing piglets.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In a previous study, we found a difference in the postnatal expression pattern of CAT-1 and CAT-2A, as well as differences in CAT-2A expression levels among LD, BF, and RH muscles (Ishida et al 2017). Here, we compared the effects of a low-protein diet and feed restriction on the expression of CAT-1 and CAT-2A among three skeletal muscles of growing piglets.…”
Section: Discussionmentioning
confidence: 74%
“…The protocols we used for total RNA extraction and quantitative real-time PCR analysis have been described previously (Ishida et al 2017). The CATs data of pigs were normalized using the geometric means of the ribosomal protein L4 (RPL4) and the TATA box-binding protein (TBP) as reference genes for skeletal muscles (Vandesompele et al 2002).…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study on chickens found that the most suitable reference gene in the liver is ribosomal protein L13 ( RPL13 ); in the jejunum it is glyceraldehyde-3-phosphate dehydrogenase ( GAPDH ), while hydroxymethylbilane synthase ( HMBS ) is compatible in all tissues ( 9 ). In pigs, HPRT1 and HMBS are reference genes for skeletal muscles and affect their postnatal growth ( 10 ). In goats, beta-actin (β -actin ) was the most stable in the stomach, small intestine, and ovary; 18S ribosomal RNA ( 18S rRNA ) in the heart and spleen; HMBS in the uterus and lungs; TATA box binding protein ( TBP ) in the liver; HPRT1 in the kidney; and GAPDH in the muscles ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…y+L+ amino acid transporter-1 (y+LAT1) is encoded by the SLC7A7 gene, and the substrates of this system are arginine, lysine, leucine, glutamine and methionine [ 8 ]. The expression level of SLC7A7 is high in intestine and kidney but low in skeletal muscle, and the mutation of SLC7A7 gene usually induces many complications, such as persistent hypotonia, birth retardation, osteoporosis, coma and mental development disorder [ 9 , 10 ]. It has been demonstrated that SLC7A7 −/− mice exhibit intrauterine growth restriction and persistent growth retardation that generates fetal growth retardation through downregulation of IGF1, thus resulting in mouse death [ 11 ].…”
Section: Introductionmentioning
confidence: 99%